2018
DOI: 10.1142/s0192415x18500295
|View full text |Cite
|
Sign up to set email alerts
|

Total Flavones ofAbelmoschus manihotExhibits Pro-Angiogenic Activity by Activating the VEGF-A/VEGFR2-PI3K/Akt Signaling Axis

Abstract: Angiogenesis is a process of new blood vessel formation from pre-existing vessels. Vascular endothelial growth factor-A (VEGF-A) binds to VEGF receptor-2 (VEGFR2) and thus activation of phosphatidylinositol 3-kinase (PI3K)/Akt pathway play a central role in angiogenesis. Total flavones of Abelmoschus manihot (TFA), the major active component of the traditional Chinese herb Abelmoschus manihot, display novel pro-angiogenic activity. However, little information concerning its underlying mechanism is available. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In the present study, we also demonstrated that the CLU‐induced suppression of spermatogenic cell autophagy and apoptosis and diabetes‐induced testicular damage were mediated by the effects of CLU on the activation of PI3K/AKT/mTOR signalling. LY294002 is a potent inhibitor of the PI3K protein family [Zhu, Tang, Lv et al., 2018] and effectively abrogated the suppression of spermatogenic cell autophagy and apoptosis caused by CLU overexpression in this study. Moreover, LY294002 was shown to markedly exacerbate testicular damage in the diabetic rat model, which established the essential roles of PI3K/AKT/mTOR signalling in CLU‐regulated spermatogenic cell functions and testicular dysfunctions associated with diabetes pathogenesis.…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, we also demonstrated that the CLU‐induced suppression of spermatogenic cell autophagy and apoptosis and diabetes‐induced testicular damage were mediated by the effects of CLU on the activation of PI3K/AKT/mTOR signalling. LY294002 is a potent inhibitor of the PI3K protein family [Zhu, Tang, Lv et al., 2018] and effectively abrogated the suppression of spermatogenic cell autophagy and apoptosis caused by CLU overexpression in this study. Moreover, LY294002 was shown to markedly exacerbate testicular damage in the diabetic rat model, which established the essential roles of PI3K/AKT/mTOR signalling in CLU‐regulated spermatogenic cell functions and testicular dysfunctions associated with diabetes pathogenesis.…”
Section: Discussionmentioning
confidence: 53%
“…VEGF is a family of homodimeric proteins that consisted by six members, including VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E and placenta growth factor [ 30 ]. VEGF-A, the most studied VEGF family member, was shown to play a pivotal role in neovascularization regulation [ 31 ]. CD34, a cell surface sialomucin, is involved in a variety of pathophysiologic processes, including cell adhesion, inflammatory cell recruitment and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin distributes in various fruits and vegetables and is one of bioflavonoid compounds of Abelmoschus plants, which has been reported as a potential therapeutic herb for the treatment of DN in our previous studies (14,15) and other studies (16,17). Quercetin shows diverse pharmacological effects, including anti-oxidation and anti-inflammatory (18,19).…”
Section: Introductionmentioning
confidence: 95%